2018
DOI: 10.3390/ijms19113454
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Muscle Function and Disease

Abstract: Circular RNAs (circRNAs) are a class of RNA produced during pre-mRNA splicing that are emerging as new members of the gene regulatory network. In addition to being spliced in a linear fashion, exons of pre-mRNAs can be circularized by use of the 3′ acceptor splice site of upstream exons, leading to the formation of circular RNA species. In this way, genetic information can be re-organized, increasing gene expression potential. Expression of circRNAs is developmentally regulated, tissue and cell-type specific, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 97 publications
(162 reference statements)
1
60
0
1
Order By: Relevance
“…In addition, lncRNA H19, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), MD1, and MyoD in skeletal muscles, respectively, sponge miR-675, Let-7 family, miR-133, and protein IMP2 to mediate myogenesis (Dey, Pfeifer, & Dutta, 2014;Gong et al, 2015;Han, Yang, Cao, & Liang, 2015;Legnini, Morlando, Mangiavacchi, Fatica, & Bozzoni, 2014). CircRNAs such as circ-ZNF609, circ-QKI, and circ-BNC2 from skeletal muscle, respectively, regulates myoblast proliferation and differentiation (Greco, Cardinali, Falcone, & Martelli, 2018;Legnini et al, 2017) by interacting with miR-133, miR-24, and miR-23 (P. . from pancreas has been shown to enhance insulin secretion via repressing miR-7 (Xu, Guo, Li, & Yu, 2015).…”
Section: Skmcs-exs From Palm Oil-induced Insulin Resistance Mice Couldmentioning
confidence: 99%
“…In addition, lncRNA H19, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), MD1, and MyoD in skeletal muscles, respectively, sponge miR-675, Let-7 family, miR-133, and protein IMP2 to mediate myogenesis (Dey, Pfeifer, & Dutta, 2014;Gong et al, 2015;Han, Yang, Cao, & Liang, 2015;Legnini, Morlando, Mangiavacchi, Fatica, & Bozzoni, 2014). CircRNAs such as circ-ZNF609, circ-QKI, and circ-BNC2 from skeletal muscle, respectively, regulates myoblast proliferation and differentiation (Greco, Cardinali, Falcone, & Martelli, 2018;Legnini et al, 2017) by interacting with miR-133, miR-24, and miR-23 (P. . from pancreas has been shown to enhance insulin secretion via repressing miR-7 (Xu, Guo, Li, & Yu, 2015).…”
Section: Skmcs-exs From Palm Oil-induced Insulin Resistance Mice Couldmentioning
confidence: 99%
“…According to their sources, circular RNAs can be divided into three types, exonic circRNAs, intronic circRNAs and exonicintronic circRNAs [14,15]. In general, most exonic circRNAs are localized in the cytoplasm and could function as a sponge for miRNAs to affect post-transcriptional regulation, which means that circRNAs could be a member of competing endogenous RNAs (ceRNAs) [16]. For instance, ciRS-7/CDR1 is regarded as the inhibitor of miR-7 to regulate hepatocellular carcinoma [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that CircRNAs are highly enriched in striated muscle, indicating that circRNAs service as a new regulatory network that contributes to skeletal muscle development, myogenesis and regeneration, etc. [16]. However, the existing research on how circular RNA affecting muscle development is relatively rare, so the study on circular RNA can help to gain a deeper understanding of the regulatory network for muscle development.…”
Section: Introductionmentioning
confidence: 99%
“…High throughput sequencing has demonstrated that circRNAs were widely and abundantly distributed in the eukaryotic transcriptome with tissue‐specific expression . Functionally, circRNAs could regulate the protein function via cap‐independent mechanism, affect the splicing of parental genes and serve as the microRNAs (miRNAs) sponges to cross‐talk with miRNAs . Emerging evidence has proven that circRNAs played important roles in the development of normal tissues and various diseases, such as cardiovascular diseases, age‐related diseases, autoimmune diseases and tumours .…”
Section: Introductionmentioning
confidence: 99%
“…20 Functionally, circRNAs could regulate the protein function via cap-independent mechanism, affect the splicing of parental genes and serve as the microRNAs (miRNAs) sponges to cross-talk with miRNAs. [21][22][23] Emerging evidence has proven that cir-cRNAs played important roles in the development of normal tissues and various diseases, such as cardiovascular diseases, age-related diseases, autoimmune diseases and tumours. [24][25][26][27][28][29][30] Their functions as potential biomarkers were gradually discovered in cancers and neurodegenerative disorders.…”
mentioning
confidence: 99%